Снежная королева: [сказка / художник Н. Фаттахова] - Фаттахова Н. (Учимся читать по слогам, 2016)
Экземпляры: ф10 (20180214) / Инвентарный номер: 55434 / Цена: 25.00 / Сис.шифр: Д / Авт.знак: С 53 / ГРНТИ: 17.82.93 / ББК: 84(0)